Action of cytochalasin D on cells of established lines. III. Zeiosis and movements at the cell surface (The Rockefeller University Press, 1975)
The projection of knobby protuberances at the cell surface (zeiosis) is a general cellular response to cytochalasin D (CD), resulting from herniation of endoplasm through undefended places of the cortex during cell contractions and displacement of microfilaments induced by CD. Zeiosis is prevented by agents that interfere with the contractile response to CD, such as inhibitors of energy metabolism or cyclic AMP. The developed protrusions, which remain relatively stable in the presence of CD, contain chiefly mono- or subribosomes, and occasionally other organelles normally resident in endoplasm; compact microfilament felt occupies their bases and extends into their proximal stalks. Protein synthesis in the knobs is less than half of that in the polyribosome-containing endoplasm residual in the main body of the cell. Knobs first protrude singly near the margin of the contracting cells and rapidly cluster into small groups in the periphery even at lower temperature. The clusters then migrate centripetally and coalesce into a large aggregate near the apex of the immobilized and retracted cell: this movement is energy- and temperature-dependent. Aggregation is more prominent and stable in cell lines of epithelial derivation than in fibroblastic or other lines in which nuclear extrusion occurs more readily. The latter is regarded as a special manifestation of zeiosis. Macromarkers, such as latex spherules, migrate like the zeiotic knobs on the cell surfaces in the presence of CD. The aggregated knobs, although persistent for days in the presence of CD, are rapidly recessed after withdrawal of the agent as ruffling is resumed and the cells spread. These movements are discussed in terms of current concepts of mobility of the cell membrane.